Recent advances in synthesizing and utilizing nitrogen-containing heterocycles - Ha, Hyun-Joon (Frontiers in Chemistry, 2023)
The use of organocatalysts and a pot economy has strengthened recent organic syntheses. Synthetic methodologies may be applicable in laboratory preparation or in the industrial production of valuable organic compounds. In most cases, synthetic challenges are overcome by highly efficient and environmentally benign organocatalysts in a pot-economical manner. This is exemplified by the recent synthesis of tetrahydropyridine-containing (−)-quinine.